Matemal separation affects cocaine-induced locomotion and response to novelty in adolescent, but not in adult rats - Marin, Marcelo Tadeu [UNESP]; Planeta, Cleopatra da Silva [UNESP] (Elsevier B.V., 2004)
Maternal separation is known to exert long-term effects on both behavior and the neuroendocrine system. We investigated cocaine-induced locomotor activation as well as the locomotor and corticosterone response to forced novelty in maternally separated adolescent and adult rats. Maternal separation consisted of separating litters from their darns daily during 5 h from postnatal days 2 to 6. Control animals were subjected only to regular cage changes. Cocaine- (10 mg/kg, i.p.) and novelty-induced locomotion were recorded in an activity cage. After the animals were tested for behavioral response to novelty, trunk blood samples were collected and plasma corticosterone levels were determined by radioimmunoassay. Adolescent rats exposed to maternal separation exhibited an increased locomotor response to novelty and cocaine; corticosterone levels were lower in these adolescent animals, after exposure to the novel environment. These effects of materrial separation were not observed in rats that were tested as adults. Thus the maternal separation protocol produced enduring but transient changes in the behavioral response to cocaine and in the stress response to novelty. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: maternal separation; cocaine; corticosterone; novelty; adolescence; early stress